Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11426-010-4098-5
|View full text |Cite
|
Sign up to set email alerts
|

A luminescent metal-organic framework with an open cubic cage and eight-coordinate cadmium nodes

Abstract: 1) Crystal data for 1: (H 4 N) 2 Cd(H 2 PA) 2 (DMF) 4 ·6H 2 O, Mr = 1321.68, monoclinic, space group Cc, a = 28.333(4) Å, b = 11.0343(15) Å, c = 20.516(3) Å,  = 120.878(3), V = 5505.0(13) Å 3 , T = 293 K, Z = 4, calcd = 1.536 g cm 3 , (Mo-K) = 0.486 mm 1 , S = 0.895, 5994 reflections measured, 4006 unique (R int = 0.0330), R 1 = 0.0734, wR 2 = 0.2454 (all data).2) Preparation and analytical data for 1: Pamoic acid (0.078 g, 0.2 mmol) was dissolved in 5 mL of DMF. 10 mL of an aqueous solution of Cd(ClO 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The document has reported that free 4,4’‐bipy ligand is almost nonfluorescent in the visible light range [29] . Therefore, the luminescence of 1 may be attributed to intraligand of H 2 L 2− or ligand‐to‐ligand charge transfer (H 2 L 2− →4,4’‐bipy or 4,4’‐bipy→H 2 L 2− ) due to the stable d 10 electronic configuration of Cd 2+ ions [30‐31] . Further calculation of CIE chromaticity coordinate for 1 indicated that compound 1 may be served as a good candidate for blue luminescent material (Figure S2 inset).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The document has reported that free 4,4’‐bipy ligand is almost nonfluorescent in the visible light range [29] . Therefore, the luminescence of 1 may be attributed to intraligand of H 2 L 2− or ligand‐to‐ligand charge transfer (H 2 L 2− →4,4’‐bipy or 4,4’‐bipy→H 2 L 2− ) due to the stable d 10 electronic configuration of Cd 2+ ions [30‐31] . Further calculation of CIE chromaticity coordinate for 1 indicated that compound 1 may be served as a good candidate for blue luminescent material (Figure S2 inset).…”
Section: Resultsmentioning
confidence: 99%
“…4,4'-bipy or 4,4'-bipy!H 2 L 2À ) due to the stable d 10 electronic configuration of Cd 2 + ions. [30][31] Further calculation of CIE chromaticity coordinate for 1 indicated that compound 1 may be served as a good candidate for blue luminescent material (Figure S2 inset).…”
Section: Luminescent Emission Spectrum Of 1 Its Sensing Property For ...mentioning
confidence: 99%
“…4 and 5 could self‐assemble to form CSP through the host–guest interaction of B21C7–SAS ( Figure ). [ 32 ] They proved that monomer concentration was a pivotal factor for the formation of CSP. Because of the stimulus‐responsiveness of host–guest interaction and the dynamic nature of disulfide bonds, the linear CSP possessed pH‐, ion‐, redox‐, and light‐response properties.…”
Section: Crown Ether‐based Supramolecular Linear Polymersmentioning
confidence: 99%
“…7 Additionally, a disulphide bond cross-linkage is now commonly used in polymerization by dynamic covalent bonds. 8 The use of the disulphide bond as the linkage structure provides stability, 9 reversibility, 10 and stimuli responsiveness 11 in dynamic smart materials. Although the disulphide linkage can be formed spontaneously under aerobic conditions, 12 this type of random air-oxidation reaction can lead to mixed disulphide aggregations.…”
Section: Introductionmentioning
confidence: 99%